New biotechnology enhances the application of cisgenesis in plant breeding - Hou, Hongwei; Atlihan, Neslihan; Lu, Zhen-Xiang (Frontiers in Plant Science, 2014)
Cisgenesis is genetic modification to transfer beneficial alleles from crossable species into a recipient plant. The donor genes transferred by cisgenesis are the same as those used in traditional breeding. It can avoid linkage drag, enhance the use of existing gene alleles. This approach combines traditional breeding techniques with modern biotechnology and dramatically speeds up the breeding process. This allows plant genomes to be modified while remaining plants within the gene pool. Therefore, cisgenic plants should not be assessed as transgenics for environmental impacts.